2014
DOI: 10.1002/jhbp.145
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-192 in liver fluke-associated cholangiocarcinoma patients: a prospective prognostic indicator

Abstract: This finding indicates that elevated levels of miR-192 may be involved in CCA genesis and have a potential utility as a noninvasive prognostic indicator for CCA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 37 publications
1
41
0
1
Order By: Relevance
“…We additionally showed that miR-192 can suppress expression of the bile acid and anticancer drug transporter OATP1B3 and the bile acid transporter OST␣/␤ in a FXR-dependent manner. It remains unclear whether restoration of miR-192 expression and the consequently diminished expression of FXR target genes would be beneficial for cancer patients, especially considering that miR-192 has been shown to possibly act as an oncogenic miRNA by downregulation of Smad interacting protein 1 in other inflammation-related cancers (21,26,35). Therefore, it can be speculated that diminished expression of the transport protein OST␣/OST␤, a heterodimer-forming bile acid transporter important for the excretion of bile acids from hepatocytes and enterocytes, may be a mechanism of intracellular bile acid accumulation promoting inflammation and/or cancer development in certain cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We additionally showed that miR-192 can suppress expression of the bile acid and anticancer drug transporter OATP1B3 and the bile acid transporter OST␣/␤ in a FXR-dependent manner. It remains unclear whether restoration of miR-192 expression and the consequently diminished expression of FXR target genes would be beneficial for cancer patients, especially considering that miR-192 has been shown to possibly act as an oncogenic miRNA by downregulation of Smad interacting protein 1 in other inflammation-related cancers (21,26,35). Therefore, it can be speculated that diminished expression of the transport protein OST␣/OST␤, a heterodimer-forming bile acid transporter important for the excretion of bile acids from hepatocytes and enterocytes, may be a mechanism of intracellular bile acid accumulation promoting inflammation and/or cancer development in certain cases.…”
Section: Discussionmentioning
confidence: 99%
“…An important role of miR-192 targeting ZEB2 mRNA has also been found in HCC (13). In contrast, certain forms of cancer, such as cholangiocarcinoma and esophageal cancer, show increased miR-192 expression during carcinogenesis (21,26).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Much attention has been given to miR-192-5p as a serum-based biomarker. As an example, miR-192-5p levels were highly elevated in various liver diseases [8,9,12,14,15] as well as in patients with cancer, where elevated serum levels are associated with tumour metastasis and poor survival [17]. In the present study, we analysed the expression of miR-192-5p in ischaemia/reperfusion (I/R) and toxin-induced liver injury.…”
mentioning
confidence: 98%
“…Moreover, elevated levels of circulating miR-26a correlated with the disease stage and were reported to be independent prognostic markers of overall and disease-free survival [70]. In a study from Thailand including patients with liver fluke-associated CCA, high levels of serum miR-192 were found to significantly correlate with lymph node metastasis and shorter overall survival [71]. However, most studies on the prognostic capabilities of miRNAs for CCA have analyzed tissue samples from tumor resection without considering serum analyses.…”
Section: Resultsmentioning
confidence: 99%